MiFID II between European rule-making and national market surveillance: the case of high-frequency trading (2020)
In line with the spirit of the regulatory reforms initiated after the outbreak of the global financial crisis in 2008, the EU reviewed its ‘Markets in Financial Instruments Directive’ (MiFID). As this was an action coordinated at the international level, this initiative allows us to look into the theoretical propositions developed in our first research perspective, that is, the ‘vertical perspective’. The revised legislative package, MiFID II, entered into force in January 2018 and consists for the most part in extending public oversight of those areas of the financial market that between the 1980s and 2000s mostly operated in the dark. More precisely, one of the key objectives of MiFID II was to introduce reporting obligations in market segments that until recently operated directly between buyers and sellers or on alternative trading venues (see Chapter 6 for two illustrative case studies).